2016
DOI: 10.1002/clc.22510
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Medical Management in Patients Undergoing Elective Cardiac Catheterization for Chronic Ischemic Heart Disease

Abstract: Background: Compared with medical therapy, percutaneous coronary intervention (PCI) does not reduce mortality or myocardial infarction in patients with stable angina. Therefore, PCI should be guided by refractory anginal symptoms and not just lesion characteristics. Hypothesis: We hypothesized that angiographic lesion characteristics and stress test results would have a greater role in the decision to proceed with PCI than would symptom severity. Methods: We performed a retrospective cohort study of patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Unlike patients with acute coronary syndromes (ACS), patients with chronic coronary artery disease (CAD) are predominantly managed in the outpatient setting, with therapies directed toward preventing cardiovascular events, improving survival, and controlling angina symptoms . Although the prevalence and treatment patterns for ACS are well known, data about the prevalence and management of angina among outpatients with chronic CAD are sparse . The American College of Cardiology outpatient Practice Innovation and Clinical Excellence (PINNACLE) registry (a national practice‐based cardiovascular quality‐improvement program sponsored by the National Cardiovascular Data Registry) has provided an important opportunity to better understand current treatment patterns and the opportunity to improve the outpatient management of cardiovascular diseases, particularly with respect to secondary prevention .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike patients with acute coronary syndromes (ACS), patients with chronic coronary artery disease (CAD) are predominantly managed in the outpatient setting, with therapies directed toward preventing cardiovascular events, improving survival, and controlling angina symptoms . Although the prevalence and treatment patterns for ACS are well known, data about the prevalence and management of angina among outpatients with chronic CAD are sparse . The American College of Cardiology outpatient Practice Innovation and Clinical Excellence (PINNACLE) registry (a national practice‐based cardiovascular quality‐improvement program sponsored by the National Cardiovascular Data Registry) has provided an important opportunity to better understand current treatment patterns and the opportunity to improve the outpatient management of cardiovascular diseases, particularly with respect to secondary prevention .…”
Section: Introductionmentioning
confidence: 99%
“…Atreya et al found objective evidence of this practice. 21 In a 2016 study of 207 patients with obstructive lesions amenable to PCI, the only factors associated with medical management were those that increased the risk of the procedure: age, chronic kidney disease, distal location of the lesion, and type C lesions (the most diffi cult ones to treat by PCI). More important, evidence of ischemia, presence of angina, and being on optimal medical therapy or maximal antianginal therapy were not associated with PCI.…”
Section: Cardiologists' Reasons For Performing Pcimentioning
confidence: 99%